Changing penologies and European crime policy: Theory and practice in the global context. Introduction: Zmieniające się penologie i europejska polityka karna. Teoria i praktyka w kontekście globalnym. Wprowadzenie (Archives of Criminology, 2023)
This Special Issue deals with the significant questions about changing penologies and European crime policy. The discussed topics cover the general picture, trends and aim of today’s European penology. The focus is paid on the effectiveness of crime policy, its role in contemporary penology and fundamental values which are closely linked with human rights orientated approach. The issue of punishment and prison standards are also presented in the context of International and European standards. Furthermore, Scandinavian approach to crime policy is widely illustrated, especially based on the Finnish and Norwegian studies.